The Contribution of the Maternal Immune System to the Establishment of Pregnancy in Cattle - Fair, Trudee (Frontiers in Immunology, 2015)
Immune cells play an integral role in effecting successful reproductive function. Indeed disturbed or aberrant immune function has been identified as primary mechanisms behind infertility. In contrast to the extensive body of literature that exists for human and mouse, studies detailing the immunological interaction between the embryo and the maternal endometrium are quite few in cattle. Nevertheless, by reviewing the existing studies and extrapolating from sheep, pig, mouse and human data we can draw a reasonably comprehensive picture of immune cell involvement from follicle development, ovulation, gamete transfer, maternal recognition of pregnancy, implantation and placentation. These events are reviewed in detailed below and key findings are discussed.